Penatalaksanaan Fisioterapi Pada Kasus Bell's Palsy Dextra Di RSUP DR. Sardjito Yogyakarta - Putranto, Alfian Ade; , Dwi Rosella Komala Sari S.Fis, M.Fis (2015)
Background : Bell's palsy is an acute paralysis in n. Peripheral Facial that is not known why (Sir Charles bell, 1821). So bell's palsy is a complaints where someone can not move his face, due to the disorder of the n. Peripheral facial. The cause of weakness n. Peripheral facial own until now has not been found. Bell's palsy generally occurs with the condition of unilateral. The cause of bell's palsy namely cold wind that goes into the foramen stylomastoideus caused nerve facial can swell and then. Swelling nerve fasialis it resulted in the blood supply to the nerve was hampered. This caused ischemic even necrosis so function conduction excitatory impulses will be interrupted and cause paralysis facial lower type of motor neurons. Aims of Research : To study about physiotherapy management to increases value muscle strength of facial and functional movements of the facial muscles in the case of bell's palsy. Result : After therapy for 6 times obtained the assessment of the power of face muscles with Manual Muscle testing, m. frontalis T1: 1 - T6: 3 and m. orbicularis oculi T1: 1 - T6: 3. While m. corrugators supercili, m. procerus, and m. orbicularis orisnot yet there is an increase. Assessment result of the functional ability face with ugo fisch scale. Movement frowning T1: 3 - T6: 7 and movement close the eyes T1: 9 - T6: 21. While at a break, movement smiled and whistling it has still not been increase in the number. Conclusion : Transcutaneus Electrical Nerve Stimulation (faradic), Massage, and Mirror exercise influence in increasing the power of face muscle and increasing the ability of functional face muscle. Keyword : Bell's Palsy, n. Peripheral Facial, Transcutaneus Electrical Nerve Stimulation (faradic), Massage, and Mirror Exercise.